Albuminated PLGA nanoparticles containing bevacizumab intended for ocular neovascularization treatment. Issue 10 (27th March 2015) - Varshochian, Reyhaneh; Riazi‐Esfahani, Mohammad; Jeddi‐Tehrani, Mahmood; Mahmoudi, Ahmad‐Reza; Aghazadeh, Sara; Mahbod, Mirgholamreza; Movassat, Morteza; Atyabi, Fatemeh; Sabzevari, Araz; Dinarvand, Rassoul
Abstract Bevacizumab, an anti‐VEGF antibody, has demonstrated trustworthy effects in treatment of retinal and choroidal neovascularization that both are crucial sight threatening conditions. However, the weak point is the short half‐life of the drug in vitreous which necessitates frequent intravitreal injections. Accordingly employing controlled‐release drug delivery systems such as polymeric nanoparticles (NPs) has been suggested. In this study albuminated‐PLGA‐NPs containing bevacizumab were prepared and studied intended for reducing the number of injections. NPs were formulated by double‐emulsion method and a single dose of NPs was intravitreally injected to rabbits. The drug concentrations in vitreous and aqueous humor were assayed in different time intervals using ELISA and intraocular pharmacokinetic parameters were calculated. Moreover, coumarin‐6 loaded albuminated‐PLGA‐NPs were employed to evaluate the distribution and persistence of the NPs in the posterior segment. Results revealed that the bevacizumab vitreous concentration maintained above 500 ng mL−1 for about 8 weeks and 3.3 times elevation was observed in the drug vitreous MRT compared with the control. According to coumarin‐6 NP tests, fluorescence emissions in posterior tissues were observed for 56 days which confirmed the nanoparticles persistence in ocular tissues during the test span. Therefore our prepared formulation may offer improvements in treatment of eye posterior segment neovascularization. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3148–3156, 2015.